1992
DOI: 10.1007/bf00010255
|View full text |Cite
|
Sign up to set email alerts
|

On the position of the digenean family Heronimidae: an inquiry into a cladistic classification of the Digenea

Abstract: Brooks, O'Grady & Glen (1985b) placed the seemingly aberrant and highly derived family Heronimidae at the base of their cladogram of the Digenea. In the absence of arguments for the composition and polarity of the putative homologous series on which their cladogram is based, it was found necessary to consider in detail almost all of their character series. In the course of my analysis I (1) argue that the oral sucker is singular to the Digenea, and that the oral sucker is not synapomorphic nor the ventral suck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 161 publications
3
30
0
1
Order By: Relevance
“…The former cluster was weakly supported (52-56% of bootstrap replicates) but is consistent with one of two alternative hypotheses proposed by Pearson (1992). Based on the presence of a terminal pharynx and oesophageal bulb Pearson (1992) argued that the gyliauchenids were more closely related to the paramphistomids than either was to the lepocreadiids.…”
Section: Phylogenetic Relationships Among Familiessupporting
confidence: 57%
See 1 more Smart Citation
“…The former cluster was weakly supported (52-56% of bootstrap replicates) but is consistent with one of two alternative hypotheses proposed by Pearson (1992). Based on the presence of a terminal pharynx and oesophageal bulb Pearson (1992) argued that the gyliauchenids were more closely related to the paramphistomids than either was to the lepocreadiids.…”
Section: Phylogenetic Relationships Among Familiessupporting
confidence: 57%
“…Phylogeny above the family level in the Digenea, however, is arguably the most controversial area in helminth systematics (Pearson, 1972(Pearson, , 1992Clark, 1974;Cable, 1974;Brooks et al, 1985, Brooks, 1989Gibson, 1987). A key problem is the paucity and widespread evolutionary convergence of characters from morphology and life-cycles.…”
Section: Introductionmentioning
confidence: 99%
“…This leads us to believe that both kinds of data are of value in inferring relationships among the Digenea. Pearson (1992) might have been overly pessimistic about the phylogenetic value of those morphological and life cycle characters identified to date within the Digenea. However, it is evident that only partial resolution of the taxa analyzed here can be achieved with the present morphological data.…”
Section: Concluding Statementmentioning
confidence: 96%
“…For the purposes of this study, we have retained family status for these taxa but otherwise regard the Hemiuroidea as containing the taxa listed by Gibson and Bray (1979), with the addition of the Didymozoidae. Pearson (1992), in a review of work by Brooks et al (1985Brooks et al ( , 1989, concluded that morphological homoplasy was extensive and that too few unambiguous synapomorphies had been identified to permit a cladistic treatment of the Digenea. Here we present the first molecular phylogeny for the Hemiuroidea, test for congruence between morphological and molecular data, and explore the evolution of some morphological characters.…”
Section: Introductionmentioning
confidence: 97%
“…Paragyliauchen is always monophyletic in all analyses and never directly related to the non-amphistomatous clade, despite the fact that it does not exhibit extreme amphistomy, in that the ventral sucker is placed non-terminally with the testes largely posterior to it (Yamaguti 1934, Machida 1984. Cable and Hunninen (1942), Cable (1956) and Yamaguti (1971) all considered the gyliauchenids close to the lepocreadiids and the latter included them within the Lepocreadiidae, whereas other authors have considered gyliauchenids closer to paramphistomes or microscaphidiids, due to the lack of an oral sucker (Ozaki 1937a, b;Pearson 1992). Much was made by Manter (1940) and Cable and Hunninen (1942) of the shared presence of the lymphatic (or paranephridial) system in gyliauchenids and lepocreadiids.…”
Section: Cadenatellinae Gibson Et Bray 1982mentioning
confidence: 99%